Psychological pedagogical organization of educational training process of paralympics with the defeat of locomotorium. - Shuba V.V (Kharkov National Pedagogical University, 2012)
Correction work is presented with paralympics with the defeat of locomotorium. The present state of existent methods and methods is analysed. The questions of development of new approaches, related to the differentiated programming in the educational training process of paralympics are considered. In an experiment 46 sportsmen (sex of men) took part with the defeat of locomotorium. Information of researches of anxiety was in-process utillized on the different stages of the psychocorrectional program. Conducted and the estimation of efficiency of the training program is described in detail. Research results complement a theory and method of physical education the new pictures of possibility of the use of the differentiated going near development of method of educational training process of paralympics. Conformities to the law of display of anxiety are set and psychocorrectional measures which are characteristic for paralympics with the defeat of locomotorium.